Vertical Structure of Tropical Deep Convective Systems at Different Life Stages From CloudSat Observations. Issue 21 (28th October 2021) - Hu, Xiaoyu; Ge, Jinming; Li, Wenxue; Du, Jiajing; Li, Qinghao; Mu, Qingyu
Abstract: CloudSat observations are used to characterize the morphologies and internal vertical structures of tropical deep convective systems (DCSs) at different life stages, that is, developing, mature, and dissipating stages according to the buoyancy at the cloud top. The DCSs are further partitioned into convective pillar, major anvil, and minor anvil and then discussed separately. The DCS exhibits an apparent mushroom‐like structure in the developing stage, with a horizontally narrow convective pillar and widespread anvil cloud. The convective pillar widens in the mature stage, while the anvil length remains quite similar. In the dissipating stage, the convective pillar shrinks vertically and horizontally, and the anvil length is shorter than that in the other two stages. The life stage has a larger impact on the vertical structure of the ice number concentration ( N ) and ice water content (IWC) than on the ice effective radius ( r e ). The high N area at the top of the convective pillar expands vertically and horizontally as the DCS evolves, indicating that newly formed ice particles are likely to accumulate in the convective pillar and consequently increase the IWC in this section rather than being transmitted to anvil clouds. Both ice and liquid precipitation occur in a narrow region within the pillar during the developing stage, then widen at the mature stage and shrink at the dissipating stage. Our results provide detailed morphologies and internal structures of DCS evolution and would be helpful to improve DCS representation in numerical models. Plain Language Summary: Clouds are important components of the Earth‐atmosphere system. Thick clouds usually reflect solar radiation back to space, cooling the system, while thin and high clouds often trap terrestrial radiation, thus warming the system. However, it is still challenging to accurately represent clouds in weather forecasting and climate prediction models. A deep convective system (DCS) normally consists of thick convective clouds and surrounding thin anvil clouds and thus has a great radiative effect on local and even global energy budgets. The rainfall generated from DCS also contributes greatly to global precipitation. In this study, we adopt three novel methods to objectively identify and analyze the vertical structure of ice clouds and precipitation particles of tropical DCSs at different life stages. The details of morphologies and vertical structures through the DCS life cycle found in this study are helpful to understand the evolution of DCSs and may help to improve DCS representation in numerical models. Key Points: Tropical deep convective systems (DCSs) are objectively identified and categorized into different life stages from CloudSat observations As DCS evolves, newly formed ice particles are likely to accumulate around convective pillars rather than being transmitted to anvil clouds Precipitation occurs in a narrow region within the pillar during developing stage, widens at mature stage and shrinks at dissipating stage